Pola Sebaran Logam Berat Kromium (Cr) Di Perairan Tulehu Maluku Tengah - Asyik Nur Allifah AF Asyik; Zamrin Jamdin; Nur Alim Natsir; Rosmawati T (Biotropic : The Journal of Tropical Biology, 2025)
Tulehu waters in Central Maluku have reportedly experienced a decline in the quality and variety of biota. Sources of pollution, including the heavy metal Chromium, are thought to have increased over time in this area. Chromium is a dangerous, toxic metal that is highly soluble and has wide mobility in nature. Pollutants that decompose in waters and settle in sediments affect the amount of uptake and sustainability of mangrove plants. The aim of this research is to determine the distribution pattern of the heavy metal Chromium during 3 measurement periods in Tulehu Waters, Central Maluku. This research was conducted on 16 May – 16 July 2024. The sampling method was carried out in three sampling periods at three observation stations. The measurement interval is 15 days. Testing for the heavy metal Chromium was carried out on water, sediment and mangrove organs using an Atomic Absorption Spectrophotometer (AAS). The results of the research show that the levels of the heavy metal Chromium in Tulehu waters fluctuated during the three observation periods and were still below the predetermined threshold, so they have not affected the life of mangrove biota but are threatening if preservation measures are not taken by the government and surrounding communities.